Diversity in the development of arts and crafts in Kazakhstan - Estauletov A.Kh., Естаулетов А.Х. (Рroblems of engineering and professional education, 2023)
In the article, many aspects of the development of handicrafts of Kazakhstan from the past to the present are considered. Features of the development of national values such as stone processing, bone carving, wood carving and carpet weaving have been revealed.